Pelvic Ectopic Adrenal Tissue Leading to Benign Gynecological Pathologies in a Mosaic Turner's Syndrome Patient: A Case Report - Aslıhan Yazıcıoğlu; Özge Senem Yücel; Mert Turğal; Ferdi Vaizoğlu; Özlem Tanas; Kemal Beksaç; Bülent Tırnaksız; Alp Usubütün; Sinan Beksaç (Medical Network, 2012)
Benign gynecological pathologies in patients with Turner's syndrome were described in the medical literature. Herein, we present a 39-year-old woman with mosaic Turner's syndrome (45,0X/46,X,i(X)q10) complaining about bleeding and persistent pelvic pain. In physical examination, she presented normal secondary sex development, normal breast, normal pubic and axillary hair. The external genitalia were also normal. Her laboratory examination showed elevated gonadotropin levels, decreased 17betaestradiol levels and normal plasma androgens and cortisol levels. At transabdominal ultrasonography multiple myoma and irregular thickening of the endometrium were suspected. At laparotomy, total abdominal hysterectomy and bilateral salpingectomy were performed. Histopathological examination revealed multiple leiomyoma, secretory endometrium and ectopically localized adrenal tissue. Since its known that both myoma uteri and secretory changes in endometrium develop primarily in woman of reproductive age and their growth is estrogen dependent, the source of estrogen in the present case was thought to be the ectopic adrenal tissue located just beneath the left salpinx. This seems to be the first report of the occurence of benign gynecological pathologies due to the ectopic adrenal tissue in a mosaic Turner's syndrome patient without hormone replacement therapy.